Development and validation of the maternal role adaptation system model (MRASM) to improve breastfeeding success - Safaah, Nurus; Munir, Miftahul; Qonitun, Umu; Qoyimah, Ilmiatus; Wijayanti, Erna Eka (Universitas Airlangga, 2025)
Introduction: The success of breastfeeding is a critical indicator of comprehensive adaptation during the maternal transition. Existing theoretical models address maternal adaptation separately, resulting in a lack of integration in predicting breastfeeding success. This research aimed to develop and validate the Maternal Role Adaptation System Model (MRASM) using Structural Equation Modeling. Methods: A cross-sectional study was conducted with 150 postpartum women recruited through purposive sampling from five community health centers in East Java, Indonesia. Eight latent constructs measured using validated instruments: focal stimuli (breast pain, fatigue, nutrition), contextual stimuli (spousal and healthcare support, information access, economic status), residual stimuli (social norms, cultural values, beliefs), coping mechanisms, emotional responses, self-concept, role function, and breastfeeding success. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via Smart-PLS 4.0. Results: The MRASM demonstrated excellent psychometric properties (Cronbach's α > 0.678, composite reliability > 0.802, AVE > 0.508). Environmental stimuli (focal, contextual, and residual) significantly influenced maternal coping mechanisms, which in turn affected emotional responses, self-concept, and role function. Emotional responses (β = 0.356, p = 0.001) and self-concept (β = 0.268, p<0.001) are the strongest predictors of breastfeeding success, explaining 26.7% of outcome variance. These findings provide healthcare professionals with specific intervention targets: managing physical symptoms, enhancing coping resources, and supporting maternal emotional well-being and self-efficacy. Conclusions: MRASM integrates Roy's and Mercer's models to address postpartum adaptation holistically, providing healthcare professionals with an evidence-based framework to support maternal role transition and breastfeeding success.